Metrology at nanoscale: thermal wave probe made it simple - Abd. Moksin, Mohd Maarof (Universiti Putra Malaysia Press, 2008)
A major hurdle facing nanotechnology implementation is in how samples of nano-scale dimensions can be probed. Parts of the problems include sample mounting, making contact with the sample; the possibility that the act of measuring alters the sample, repeatability and accuracy of measurement and referencing reference metrology to calibrate various tools to perform required measurements. The present attempted solution is certainly not a one-size-fits-all matter and no more than a complement to existing tools available such as SEM, TEM, AFM etc, which are no match for the simplicity of the thermal wave probe. Initially the thermal wave probe was not intended for nano-scale applications. The discovery of the converging thermal wave mechanism in thin subsurface layers opened up avenues for stand alone thin layer probing even for materials of high thermal conductivity and diffusivity like copper and silver. This came in tandem with the advent of nano-materials whereby electronic packaging materials could include thin layers with thermal diffusivity exceeding that of copper to alleviate problems associated with overheating. From the time the converging thermal wave technique was introduced in the mid eighties until very recently, it could only be performed with the availability of massive and expensive ultra-short lasers even though the thinnest material that could be measured was 30 μm. With the birth of the CTWaveProbeTM this myth should no longer exist. Within the limitations of standard samples available the CTWaveProbeTM has measured samples of thickness as low as 0.75 μm. In the near future everyone can perform nano-scale measurement like everyone now can fly!